Growth, yield and economics of fodder maize (Zea mays) as influenced by Jeevamrutha formulations under varying nutrient levels - S K, MANJUNATHA; KUMAR, RAKESH; RAM, HARDEV; MEENA, R K; YADAV, M R; MAKARANA, GOVIND; KUMAR, UTTAM (The Indian Journal of Agricultural Sciences, 2022)
A split plot experiment was conducted at research farm of Agronomy Section, ICAR–National Dairy Research Institute, Karnal, Haryana during kharif 2018–19 to evaluate various jeevamrutha formulations under the varying nutrient levels in fodder maize (Zea mays L.). In main plot four nutrient levels [Control (0), 50, 75 and 100% RDF] and in sub-plot, five jeevamrutha formulations [Control (without jeevamrutha), water based jeevamrutha @1000 l/ha, water based jeevamrutha @1500 l/ha, whey based jeevamrutha @1000 l/ha and whey based jeevamrutha @1500 l/ha] were taken as treatments and replicated thrice. Better growth attributes, viz. plant height, number of leaves per plant, stem girth and leaf:stem ratio were observed with increased nutrient levels. Application of 50, 75 and 100% RDF resulted in 35.01, 61.21 and 74.19% higher green fodder yield (GFY) over control. Jeevamrutha (whey/water based) formulations significantly improved growth. Significantly higher dry matter yield (DMY) (11.65 t/ha) was obtained with 100% RDF. Whey based jeevamrutha formulation @1500 l/ha ((52.83 and 11.09 t/ha) closely followed by water based jeevamrutha formulation @1500 l/ha (51.38 and 10.79 t/ha) resulted in higher GFY and DMY, respectively. The highest gross returns and net returns were obtained in 100% RDF with whey based jeevamrutha @1500 l/ha (`94.89 and 70.32 × 103/ha, respectively). Maximum benefit:cost ratio (2.89) was recorded in 100% RDF and water based jeevamrutha formulation @1500 l/ha. Interaction effect between jeevamrutha formulation and nutrient levels suggested that application of jeevamrutha formulation @1500 l/ha in both forms (Whey and water) can save 25% nutrient dose.